1998
DOI: 10.1142/s0218127498001029
|View full text |Cite
|
Sign up to set email alerts
|

Chaos: An Ecological Reality?

Abstract: Deterministic chaos has been studied extensively in various fields. Some of the ideas emerging out of these studies have been put to novel applications. However, it is unknown whether natural ecological systems support chaotic dynamics. There is no concrete evidence which suggests that ecosystem evolution is chaotic in certain situations. This is very intriguing because ecosystems do possess all the necessary qualifications to be able to support such a dynamical behavior. The present paper attempts to answer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 19 publications
0
38
0
1
Order By: Relevance
“…Although ecological models were among the first examples of chaos, 35 it was often argued that chaos should disappear when more ecological details are taken into account. 36,37 By application of generalized models it has been shown that double Hopf bifurcations generally exist in food chains with more than three trophic levels.…”
Section: Some Results On Global Dynamicsmentioning
confidence: 99%
“…Although ecological models were among the first examples of chaos, 35 it was often argued that chaos should disappear when more ecological details are taken into account. 36,37 By application of generalized models it has been shown that double Hopf bifurcations generally exist in food chains with more than three trophic levels.…”
Section: Some Results On Global Dynamicsmentioning
confidence: 99%
“…Predatorprey interaction is the most common. There are two types of predators: (i) specialists and (ii) generalists [8][9][10][11][12][13][14][15][16][17][18][19][20]. A specialist predator feeds only one food.…”
Section: Specialist and Generalist Predators Our Modelmentioning
confidence: 99%
“…One question that has been discussed in the ecological literature for quite some time is whether chaotic dynamics occur in natural food webs (May 1987;Upadhyay et al 1998;Rai and Schaffer 2001). On the one hand, even some of the simplest ecological models exhibit chaotic dynamics (e.g., May 1974May , 1976Edwards and Yool 2000).…”
Section: Equivalence Of More Complex Food Websmentioning
confidence: 99%